Dinamica publicațiilor sociologice ale ICCV: 1990-2019. O notă de cercetare - Voicu, Bogdan; Neguț, Adriana; Tufă, Laura; Gheondea, Alexandra (Calitatea Vieții, 2010)
This research notes analyses the dynamics of the academic production of the RIQL, as reflected by the published sociological papers and books. The Research Institute for Quality of Life is part of the Romanian Academy, and its vocation is to produce top quality studies in the social sciences. 2009 marked the 20th year of existence for RIQL, a good reason for retrospective and reflexive analyses. Our research note sketches the main trajectories followed by RIQL’s research interests, and describes how some research themes increased their relative salience, while others knew periods when they become less important. We also focus on the type of academic dissemination – through journals or books, published in Romanian or in foreign publications. The paper proposes input information which may be useful for understanding the context of the current social research in Romania.